Supported catalyst, preparation method thereof and application of supported catalyst in dry reforming reaction of methane and carbon dioxide under catalytic high-pressure condition

By using supported catalysts in the catalyst, including MgAl2O4 support and supported Au particles and transition metals, the problem of insufficient resistance to carbon deposits under high pressure conditions is solved, and the long-term stable operation of the catalyst in the dry reforming reaction between methane and carbon dioxide is achieved.

CN119869555AActive Publication Date: 2025-04-25EAST CHINA UNIV OF SCI & TECH

Patent Information

Application Number
CN202510352183.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-25
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

The existing catalysts have problems of insufficient carbon deposit resistance and poor stability in the dry reforming reaction between methane and carbon dioxide under high pressure conditions, resulting in catalyst deactivation and carbon deposit deposition.

Method used

Using a supported catalyst, including a MgAl2O4 support and a metal component supported on its surface, the metal component including Au particles and transition metal Ni or Co dispersed on the surface of Au particles, is prepared by multiple impregnation methods to form a highly dispersed structure to reduce the step position of carbon deposits.

Benefits of technology

The supported catalyst exhibits excellent anti-carbon deposit and sintering properties under high pressure conditions, can maintain the stability of long reaction cycles, and avoids deactivation of the catalyst and carbon deposit deposition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869555A_ABST
    Figure CN119869555A_ABST
Patent Text Reader

Abstract

The invention provides a supported catalyst, a preparation method thereof and application of the supported catalyst in a dry reforming reaction of methane and carbon dioxide under a catalytic high-pressure condition, and relates to the technical field of catalysts and synthesis gas preparation through methane reforming. The supported catalyst provided by the invention comprises a MgAl2O4 carrier and metal components supported on the surface of the MgAl2O4 carrier, the metal components comprise Au particles and transition metal dispersed on the surfaces of the Au particles, and the transition metal is Ni or Co. According to the supported catalyst provided by the invention, Au particles are used as dispersed metals of active metals Ni and Co, Ni and Co are highly dispersed on the surfaces of the Au particles to form a highly dispersed catalyst, and the overall area of the active metals is effectively reduced. The supported catalyst is used for catalyzing a high-pressure methane-carbon dioxide dry reforming reaction, has anti-carbon deposition and anti-sintering performance under a high-pressure harsh condition, and can realize long-period stable operation of the reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyst and methane reforming to produce synthesis gas, and in particular to a supported catalyst and a preparation method thereof and application in dry reforming reaction of methane and carbon dioxide under catalytic high pressure conditions. Background Art

[0002] Methane (CH4) is not only the main component of natural gas (including oil and gas fields, coalbed methane, shale gas and combustible ice, etc.), but also the main greenhouse gas. The simultaneous conversion of CH4 and CO2 into synthesis gas with a wide range of uses has outstanding advantages such as high resource utilization, low energy consumption and operating costs. The synthesis gas produced has a low CO / H2 ratio and is suitable as a feed gas for olefin hydroformylation and the production of acetic acid, dimethyl ether, olefins, etc. This conversion process has attractive prospects, but the main bottleneck problem is that the catalyst is unstable, easily deactivated by carbon deposition and sintered at high temperatures.

[0003] Existing methane-CO2 reforming (dry reforming, DRM) catalysts and their stability research are mainly focused on atmospheric pressure reaction conditions. The high-pressure raw gas needs to be depressurized, and the synthesis gas after the reaction needs to be pressurized for downstream processes, and gas compression is a high-energy unit operation. Considering that methane and carbon dioxide raw gases are mainly stored in high-pressure storage tanks, and the subsequent conversion of downstream synthesis gas also needs to be carried out in a high-pressure reactor, methane-CO2 reforming under high pressure is more economical. At the same time, high pressure also means higher capacity and smaller gas volume, as well as lower investment and operating costs, and saves investment in compression equipment. Therefore, the industry expects the catalyst to operate under a certain pressure (optimal 7~28atm), and the recent development trend of methane reforming catalysts is also increasingly inclined to explore how to achieve methane-CO2 reforming under high-pressure reaction conditions.

[0004] While the reforming reaction is taking place, it is also accompanied by three carbon deposition side reactions: methane decomposition, CO disproportionation (Boudouard reaction), CO hydrogenation, and reverse water gas shift reaction. From thermodynamic analysis, it can be seen that methane decomposition is the main carbon deposition reaction under high temperature and high pressure, and the carbon elimination reaction mainly comes from the reaction of CO2 and H2O with surface carbon. Although pressurization has higher industrial economic efficiency, it also puts forward higher requirements for catalyst design. For endothermic and volumetric reforming reactions, it means that the reaction temperature (>800℃) needs to be increased to achieve a sufficient conversion rate. High temperature and high pressure will bring three challenges: (1) Non-catalytic gas-phase cracking of methane will occur at high temperature. Although the decomposition of methane is negligible at normal pressure, the increase in pressure increases the collision probability between gas molecules, increases the rate of non-catalytic cracking to generate carbon precursors (acetylene, olefins and aromatics, etc.), and accelerates the carbon deposition on the catalyst surface; (2) Increasing pressure is thermodynamically favorable to carbon deposition and unfavorable to carbon removal reaction; (3) For most metal surfaces, the catalytic dissociation of methane at normal pressure is the rate-determining step of the surface reforming reaction and carbon deposition process, and the carbon deposition rate shows a first-order relationship with the methane partial pressure; with the increase of reaction temperature and methane partial pressure, the surface carbon accumulation rate increases significantly, which easily makes the carbon removal reaction the kinetically rate-determining step, resulting in surface carbon accumulation and catalyst deactivation.

[0005] Although there have been a lot of reports on methane dry reforming research, most of the reported results are based on atmospheric pressure evaluation and related catalytic research. For example, the Calcor process (OIL GAS European Magazine, 2001, 3, 44-46.) has been industrially demonstrated, mainly for the production of CO-rich synthesis gas; to prevent carbon deposition, a normal pressure process is used, and the CO2 concentration is increased in the feed gas, so that the H2 / CO ratio in the single-pass product can reach 0.43. This makes it necessary to compress the synthesis gas in downstream production, and if the H2 / CO ratio is close to 2, compression becomes more difficult. Other processes are similar. Developing suitable catalysts to enable methane dry reforming to operate for a long period of time under high pressure is an urgent need and an important challenge for the resource utilization of methane. Summary of the invention

[0006] In view of this, the object of the present invention is to provide a supported catalyst and a preparation method thereof and an application thereof in catalyzing a dry reforming reaction of methane and carbon dioxide under high pressure conditions. The supported catalyst provided by the present invention shows excellent anti-carbon deposition performance in the dry reforming reaction of methane and carbon dioxide under high pressure conditions and can maintain reaction stability over a long reaction period.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The invention provides a supported catalyst, comprising a MgAl2O4 carrier and a metal component supported on the surface of the MgAl2O4 carrier, wherein the metal component comprises Au particles and a transition metal dispersed on the surface of the Au particles, wherein the transition metal is Ni or Co, and the molar ratio of the transition metal to the Au particles is (0.5-5):100, and the mass content of the transition metal in the supported catalyst is greater than 0.006% and less than 0.06%.

[0008] Preferably, the particle size of the supported catalyst is 10-300 nm, and the particle size of the transition metal in the supported catalyst is 1-50 nm.

[0009] The present invention provides a method for preparing the supported catalyst described in the above technical solution, comprising the following steps: Mixing urea, a soluble aluminum salt, a soluble magnesium salt and water for hydrothermal reaction to obtain a precipitate; The precipitate is sequentially dried and first calcined to obtain a MgAl2O4 carrier; The MgAl2O4 carrier is mixed with a soluble gold source and water for a first impregnation, and then concentrated, dried and second calcined in sequence to obtain a MgAl2O4 carrier loaded with Au; The Au-loaded MgAl2O4 carrier is mixed with the soluble salt of the transition metal and water for a second impregnation, and then concentrated, dried and calcined for a third time in sequence to obtain the supported catalyst; the second calcination and the third calcination are both carried out in a reducing atmosphere.

[0010] Preferably, the molar ratio of the urea, the aluminum element in the soluble aluminum salt, and the magnesium element in the soluble magnesium salt is (2-4):2:1; the temperature of the hydrothermal reaction is 120-140° C., and the time is 12-16 hours.

[0011] Preferably, the first calcination includes a first stage and a second stage performed sequentially, the temperature of the first stage is 400-550° C., the insulation time is 1-2 hours, and the temperature of the second stage is 600-900° C., the insulation time is 6-8 hours.

[0012] Preferably, the first impregnation time is 2-5 hours; the second calcination temperature is 600-900° C., and the insulation time is 6-8 hours.

[0013] Preferably, the second impregnation time is 2-5 hours; the third calcination temperature is 600-900° C., and the insulation time is 6-8 hours.

[0014] Preferably, the reducing atmosphere is a mixture of hydrogen and argon, and the volume percentage of hydrogen in the mixture is 10%.

[0015] The present invention provides the use of the supported catalyst described in the above technical scheme or the supported catalyst prepared by the preparation method described in the above technical scheme in the dry reforming reaction of methane and carbon dioxide under catalytic high-pressure conditions, wherein the pressure of the dry reforming reaction of methane and carbon dioxide is 1-20 bar and the temperature is 800-900°C.

[0016] Preferably, in the dry reforming reaction of methane and carbon dioxide, the volume ratio of CH4 to CO2 is 1:1, and the space velocity GHSV is 3030~30300scc·gcat -1 ·h -1 .

[0017] The present invention provides a supported catalyst, including a MgAl2O4 carrier and a metal component loaded on the surface of the MgAl2O4 carrier, wherein the metal component includes Au particles and a transition metal dispersed on the surface of the Au particles, wherein the transition metal is Ni or Co, and the molar ratio of the transition metal to the Au particles is (0.5~5):100, and the mass content of the transition metal in the supported catalyst is greater than 0.006% and less than 0.06%. In the supported catalyst provided by the present invention, Au particles are used as dispersed metals of active metals Ni and Co, and Ni and Co are highly dispersed on the surface of Au particles to form a highly dispersed catalyst, which effectively reduces the overall area (Ensemble size) of active metals Ni and Co, and the reduction of the overall area of ​​Ni and Co means a reduction in the number of step positions suitable for carbon deposition, thereby contributing to the anti-carbon deposition effect under high temperature and high pressure. The supported catalyst provided by the present invention is used to catalyze high-pressure methane-carbon dioxide dry reforming reaction, and it has anti-carbon deposition and anti-sintering performance under the harsh conditions of high-pressure methane-carbon dioxide dry reforming reaction, and can achieve long-term stable operation of this reaction.

[0018] The results of the examples show that the supported catalyst provided by the present invention can stably operate for 100 h under high pressure (20 bar) methane-carbon dioxide dry reforming reaction conditions, and no whisker-like carbon deposits are found on the catalyst after the reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The fresh catalyst Co of Example 1-2 0.005 -Au1 / MgAl2O4、Ni 0.005 -XRD characterization diagram of Au1 / MgAl2O4 and fresh catalysts Co / MgAl2O4 and Ni / MgAl2O4 of comparative examples 1-2; Figure 2 Fresh catalyst Co 0.005 -Au1 / MgAl2O4、Ni 0.005 -SEM / Mapping (spectral scanning) image of Au1 / MgAl2O4, Figure 2 a~h correspond to fresh catalyst Co in Example 1 0.005 -Au1 / MgAl2O4, i~p corresponds to fresh catalyst Ni in Example 2 0.005 -Au1 / MgAl2O4; Figure 3 For the reaction conditions, Example Co 0.005 -Au1 / MgAl2O4(a),Ni 0.005 -Au1 / MgAl2O4(b) and comparative examples Co / MgAl2O4(c), Ni / MgAl2O4(d), Co1-Au 0.03 / MgAl2O4(e) and Ni1-Au 0.03 / High-pressure evaluation diagram of MgAl2O4(f); Figure 4 Example catalyst Co 0.005 -Au1 / MgAl2O4、Ni 0.005 -XRD characterization diagram of Au1 / MgAl2O4 after reaction with comparative catalysts Co / MgAl2O4 and Ni / MgAl2O4; Figure 5 Example catalyst Co 0.005 -Au1 / MgAl2O4、Ni 0.005 -Thermogravimetric curve (TGA) of Au1 / MgAl2O4 after reaction with comparative catalysts Co / MgAl2O4 and Ni / MgAl2O4, Figure 5 (a) is CO2-TGA, (b) is Air-TGA. DETAILED DESCRIPTION

[0020] The present invention provides a supported catalyst, comprising a MgAl2O4 carrier and a metal component supported on the surface of the MgAl2O4 carrier, wherein the metal component comprises Au particles and a transition metal dispersed on the surface of the Au particles, wherein the transition metal is Ni or Co, and the molar ratio of the transition metal to the Au particles is (0.5-5):100, and the mass content of the transition metal in the supported catalyst is greater than 0.006% and less than 0.06%.

[0021] In the present invention, the molar ratio of the transition metal to the Au particles can be 0.5:100, 1:100, 2:100, 3:100, 4:100 or 5:100; the mass content of the transition metal in the supported catalyst can be 0.01%, 0.02%, 0.03%, 0.04% or 0.05%.

[0022] In the present invention, the particle size of the supported catalyst is preferably 10-300 nm, and the particle size of the transition metal in the supported catalyst is preferably 1-50 nm.

[0023] In the present invention, the supported catalyst is represented as M-Au / MgAl2O4 (M = Ni or Co). In the supported catalyst provided by the present invention, Ni and Co are used as active metals, Au is used as the dispersed metal of Ni and Co (Ni, Co and Au are immiscible), Ni and Co are highly dispersed on the surface of Au particles, forming a highly dispersed structure, inhibiting the nucleation and growth of carbon deposits on the metal surface, and showing excellent anti-carbon deposition and anti-sintering properties under high temperature and high pressure harsh reaction conditions.

[0024] The present invention provides a method for preparing the supported catalyst described in the above technical solution, comprising the following steps: Mixing urea, a soluble aluminum salt, a soluble magnesium salt and water for hydrothermal reaction to obtain a precipitate; The precipitate is sequentially dried and first calcined to obtain a MgAl2O4 carrier; The MgAl2O4 carrier is mixed with a soluble gold source and water for a first impregnation, and then concentrated, dried and second calcined in sequence to obtain a MgAl2O4 carrier loaded with Au; The Au-loaded MgAl2O4 carrier is mixed with the soluble salt of the transition metal and water for a second impregnation, and then concentrated, dried and calcined for a third time in sequence to obtain the supported catalyst; the second calcination and the third calcination are both carried out in a reducing atmosphere.

[0025] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known in the art.

[0026] The invention comprises mixing urea, a soluble aluminum salt, a soluble magnesium salt and water to carry out a hydrothermal reaction to obtain a precipitate.

[0027] In the present invention, the soluble aluminum salt may be Al(NO3)3·9H2O, the soluble magnesium salt may be Mg(NO3)2·6H2O, and the water is preferably deionized water. In the present invention, the molar ratio of the aluminum element in the urea and the soluble aluminum salt to the magnesium element in the soluble magnesium salt is preferably (2-4):2:1, and may be 2:2:1, 3:2:1 or 4:2:1; the present invention has no special requirements for the amount of water, as long as the urea, the soluble aluminum salt and the soluble magnesium salt are fully dissolved, and the amount of water added will not affect the formation of the MgAl2O4 carrier. In the present invention, the urea provides an alkaline synthesis environment, and the addition of urea affects the dispersion of the carrier in the synthesis. The present invention controls the molar ratio of the aluminum element in the urea, soluble aluminum salt and the magnesium element in the soluble magnesium salt within the above range, and can produce a pure phase spinel structure with a large specific surface area and a small particle size; while the addition of excessive urea will lead to lattice defects, and insufficient urea will cause Al2O3 to exist in the product. In an embodiment of the present invention, urea, soluble aluminum salt and soluble magnesium salt are placed in a container, and water is added thereto and stirred for 3 hours to fully dissolve.

[0028] In the present invention, the temperature of the hydrothermal reaction is preferably 120-140°C, and may be 120, 130 or 140°C. The time is preferably 12-16 hours, and may be 12, 13, 14, 15 or 16 hours. In the embodiment of the present invention, a container containing a mixed solution of urea, a soluble aluminum salt, a soluble magnesium salt and water is transferred to a polytetrafluoroethylene liner, loaded into a pressure-resistant reactor, and the hydrothermal reaction is carried out. During the hydrothermal reaction, urea is thermally decomposed to produce NH4 in the solution. + , providing an alkaline environment in the solution, Al 3+ Mg 2+ With OH - Compared with the ammonia precipitation method under normal pressure, a slightly excess amount of urea can ensure that the solution has a suitable alkalinity, so that the added Al 3+ Mg 2+ The precipitation is sufficient and no aluminate is produced in the solution, which ensures that there is no significant difference in the chemical composition between the actual product and the target product.

[0029] After the hydrothermal reaction is completed, the present invention preferably cools the obtained reaction solution and allows it to stand for 4 hours, and then sequentially performs solid-liquid separation and solid phase washing to obtain the precipitate. The present invention has no special requirements for the solid-liquid separation method, and a solid-liquid separation method well known to those skilled in the art can be used, such as suction filtration; the solid phase washing is preferably rinsed with deionized water multiple times.

[0030] After obtaining the precipitate, the present invention sequentially dries and performs a first calcination on the precipitate to obtain a MgAl2O4 carrier.

[0031] In the present invention, the drying temperature is preferably 90°C, the time is preferably 24h, and the drying is preferably carried out in an oven. In the present invention, the dried precipitate is preferably ground into powder, placed in a SiC crucible, and placed in a muffle furnace for the first calcination. In the present invention, the first calcination is carried out in an air atmosphere; the first calcination preferably includes a first stage and a second stage carried out in sequence; the temperature of the first stage is preferably 400~550°C, which can be 400, 450, 500 or 550°C, and the holding time is preferably 1~2h, which can be 1, 1.5 or 2h; the temperature of the second stage is preferably 600~900°C, which can be 800, 850 or 900°C, and the holding time is preferably 6~8h, which can be 6, 7 or 8h; the heating rate from room temperature to the temperature of the first stage, and the heating rate from the temperature of the first stage to the temperature of the second stage are preferably 3°C / min. The first stage mainly removes the bound water in the product and decomposes the remaining urea; in the second stage, magnesium oxide and aluminum oxide gradually form a stable spinel structure. After the first calcination is completed, the mixture is cooled to room temperature to obtain a pure phase MgAl2O4 carrier.

[0032] The MgAl2O4 carrier prepared by the invention has a high specific surface area and has no phase separation under high temperature and high pressure reforming reaction conditions.

[0033] After obtaining the MgAl2O4 carrier, the present invention mixes the MgAl2O4 carrier with a soluble gold source and water for a first impregnation, and then sequentially concentrates, dries and second calcines to obtain the MgAl2O4 carrier loaded with Au.

[0034] In the present invention, the soluble gold source may be tetrachloroauric acid (HAuCl4), and the water is preferably deionized water. In an embodiment of the present invention, the method of mixing the MgAl2O4 carrier with the soluble gold source and water is as follows: placing the soluble gold source and the MgAl2O4 carrier in a container, and adding water thereto. In the present invention, the time of the first impregnation is preferably 2 to 5 hours, and may be 2, 3, 4 or 5 hours, and the first impregnation is preferably carried out under stirring.

[0035] In the present invention, the concentration method is preferably rotary evaporation, and the rotary evaporation is preferably a 70°C water bath negative pressure rotary evaporation, which is subject to spin drying; while the concentration, the components can be evenly distributed, and there is also a preliminary drying effect to form a precursor of the target catalyst. In the present invention, the drying temperature is preferably 90°C, the time is preferably 16h, and the drying is preferably carried out in an oven. After the drying, the present invention preferably grinds the obtained product into powder, pours the powder into a SiC crucible, and places it in a tube furnace for the second calcination. In the present invention, the temperature of the second calcination is preferably 600~900°C, which can be 600, 700, 800 or 900°C, the holding time is preferably 6~8h, which can be 6, 7 or 8h, and the heating rate from room temperature to the temperature of the second calcination is preferably 2°C / min; the second calcination is carried out in a reducing atmosphere, and the reducing atmosphere is preferably a mixture of hydrogen and argon, and the volume percentage of hydrogen in the mixture is preferably 10%. During the second calcination process, the Au precursor first removes bound water and further decomposes at high temperature to form Au single substance dispersed on the surface of the MgAl2O4 carrier.

[0036] After the second calcination is completed, the calcined product is preferably cooled and then ground to obtain the Au-loaded MgAl2O4 carrier, which is recorded as Au / MgAl2O4.

[0037] After obtaining the Au-loaded MgAl2O4 carrier, the present invention mixes the Au-loaded MgAl2O4 carrier with the soluble salt of the transition metal and water for a second impregnation, and then sequentially concentrates, dries and thirdly roasts to obtain the supported catalyst.

[0038] In the present invention, the transition metal is Ni or Co, and the soluble salt of the transition metal can be nickel nitrate (Ni(NO3)2), nickel acetate, cobalt nitrate (Co(NO3)2), cobalt acetate. In an embodiment of the present invention, the soluble salt of the transition metal is added in the form of a hydrate; the water is preferably deionized water. In an embodiment of the present invention, the method of mixing the Au-loaded MgAl2O4 carrier with the soluble salt of the transition metal and water is preferably: adding the Au-loaded MgAl2O4 carrier and the soluble salt of the transition metal to a container, and adding water thereto. In the present invention, the time of the second impregnation is preferably 2 to 5 hours, and can be 2, 3, 4 or 5 hours, and the second impregnation is preferably carried out under stirring.

[0039] In the present invention, the concentration method is preferably rotary evaporation, and the rotary evaporation is preferably 70°C water bath negative pressure rotary evaporation, subject to spin drying; the drying temperature is preferably 90°C, the time is preferably 16h, and the drying is preferably carried out in an oven. In the present invention, the temperature of the third roasting is preferably 600~900°C, which can be 600, 700, 800 or 900°C, the holding time is preferably 6~8h, which can be 6, 7 or 8h, and the heating rate from room temperature to the temperature of the third roasting is preferably 2°C / min; the third roasting is carried out in a reducing atmosphere, and the reducing atmosphere is preferably a mixture of hydrogen and argon, and the volume percentage of hydrogen in the mixed gas is preferably 10%; in an embodiment of the present invention, the third roasting is carried out in a tubular furnace. During the third roasting process, the soluble salt of the transition metal decomposes, and in the reducing atmosphere, the decomposition product is swept away by the reducing atmosphere. At the same time, due to being in a reducing atmosphere, the active metal is directly reduced to a single substance Co or Ni, and is loaded on Au / MgAl2O4 to form a highly dispersed structure.

[0040] After the third calcination, the present invention preferably cools the obtained product and then grinds it to obtain the supported catalyst.

[0041] The present invention adopts a step-by-step impregnation method, first prepares Au / MgAl2O4, and then loads active metal Co or Ni on Au / MgAl2O4 to form a highly dispersed catalyst M-Au / MgAl2O4 in which Co or Ni is highly dispersed on the surface of Au particles. If direct impregnation (i.e., one-step impregnation) is adopted, active metal Co or Ni will be wrapped inside by a large amount of Au, which greatly reduces the catalytic performance. The present invention has no special requirements for the amount of MgAl2O4 carrier and soluble gold source during the first impregnation, and the amount of MgAl2O4 carrier loaded with Au and the soluble salt of the transition metal during the second impregnation, and ensures that the molar ratio of the transition metal to the Au particles can be prepared to be (0.5-5): 100, and the mass content of the transition metal in the supported catalyst is greater than 0.006% and less than 0.06%.

[0042] The present invention provides the use of the supported catalyst described in the above technical solution or the supported catalyst prepared by the preparation method described in the above technical solution in the dry reforming reaction of methane and carbon dioxide under catalytic high-pressure conditions.

[0043] In the present invention, the pressure of the dry reforming reaction of methane and carbon dioxide is 1-20 bar, and may be 5, 10, 15 or 20 bar, and the temperature is 800-900°C, and may be 800, 850 or 900°C.

[0044] In the present invention, in the dry reforming reaction of methane and carbon dioxide, the volume ratio of CH4 to CO2 is preferably 1:1, and the space velocity GHSV is preferably 3030~30300 scc·gcat -1 ·h -1 , can be 6060scc·gcat -1 ·h -1 In the dry reforming reaction of methane and carbon dioxide, H2 is preferably introduced to maintain the reduced state of the active components on the catalyst surface. The introduced H2 will not affect the reaction equilibrium. The volume of H2 is preferably 1% of the total volume of CH4, CO2 and H2.

[0045] In the present invention, the dry reforming reaction of methane and carbon dioxide is the reaction of methane and carbon dioxide to generate carbon monoxide and hydrogen.

[0046] The supported catalyst provided by the present invention can maintain reaction stability over a long reaction period in a high-pressure methane-carbon dioxide dry reforming reaction, does not generate carbon deposits, and has excellent anti-carbon deposition performance and stability.

[0047] In order to further illustrate the present invention, the supported catalyst provided by the present invention, its preparation method and its application in the dry reforming reaction of methane and carbon dioxide under catalytic high-pressure conditions are described in detail below in conjunction with examples, but they should not be understood as limiting the scope of protection of the present invention.

[0048] The preparation method of the MgAl2O4 carrier in each embodiment and comparative example is as follows: Urea, Al(NO3)3·9H2O and Mg(NO3)2·6H2O were weighed in a molar ratio of 0.12:0.06:0.03, put into a beaker, and added with deionized water and stirred for 3 hours to fully dissolve; the beaker containing the solution was transferred to a polytetrafluoroethylene liner, placed in a pressure-resistant reactor and heated at 140°C for 14 hours, and then allowed to stand for 4 hours after cooling; the mixture in the liner was filtered, rinsed with deionized water several times, and the precipitate was poured into a watch glass and dried in a 90°C oven for 24 hours; after drying, it was ground into powder, put into a SiC crucible, and placed in a muffle furnace for calcination (air atmosphere): after calcination at 500°C for 1 hour, the temperature was continuously raised to 850°C and calcined for 6 hours (heating rate of 3°C / min), and then cooled to room temperature to obtain a pure phase MgAl2O4 carrier.

[0049] Example 1 Preparation of supported catalyst Co by multiple impregnation method 0.005 -Au1 / MgAl2O4 (based on the total molar amount of Au and MgAl2O4, the molar content of Au is 20%), Au=25.7032wt%, Co=0.0385wt%, MgAl2O4=74.2584wt% in the catalyst. The preparation steps are as follows: 0.7719 g of tetrachloroauric acid (99.9%, Au: 50%) and 1.1139 g of MgAl2O4 carrier were placed in a beaker, and 100 mL of deionized water was added and stirred for 3 h to fully dissolve; the solution was transferred to a 500 mL round-bottom flask, and evaporated in a water bath at 70 ° C under negative pressure. After spin drying, the flask was placed in an oven at 90 ° C for 16 h, and the flask was scraped and ground to powder; the powder was poured into a SiC crucible, placed in a tubular furnace, and heated from room temperature to 700 ° C at a rate of 2 ° C / min in a 10 vol.% H2 / Ar atmosphere, maintained for 6 h and slowly cooled, and the product was ground to obtain Au / MgAl2O4.

[0050] Loading metal Co: The above product (Au / MgAl2O4) and 0.0025g of cobalt acetate tetrahydrate (99.5%) were added to a beaker, and 100mL of deionized water was added and stirred for 3h. The solution was transferred to a 500mL round-bottom flask, and evaporated under negative pressure in a water bath at 70℃. After spin drying, the flask was placed in an oven at 90℃ and dried for 16h. The flask was scraped and the powder was ground. The powder was poured into a SiC crucible, placed in a tubular furnace, and heated from room temperature to 700℃ at a rate of 2℃ / min in a 10vol.% H2 / Ar atmosphere, maintained for 6h, and slowly cooled, and ground to obtain a supported catalyst, namely Co. 0.005 -Au1 / MgAl2O4.

[0051] Example 2 Preparation of supported Ni catalyst by multiple impregnation method 0.005 -Au1 / MgAl2O4 (based on the total molar amount of Au and MgAl2O4, the molar content of Au is 20%), Au=25.7032wt%, Ni=0.0383wt%, MgAl2O4=74.2585wt% in the catalyst. The preparation steps are as follows: 0.7719 g of tetrachloroauric acid (99.9%, Au: 50%) and 1.1139 g of MgAl2O4 carrier were placed in a beaker, and 100 mL of deionized water was added and stirred for 3 h to fully dissolve; the solution was transferred to a 500 mL round-bottom flask, and vacuum evaporated in a water bath at 70 ° C. After being dried, the flask was placed in an oven at 90 ° C for 16 h, and the flask was scraped and ground to powder; the powder was poured into a SiC crucible, placed in a tubular furnace, and heated from room temperature to 700 ° C at a rate of 2 ° C / min in a 10 vol.% H2 / Ar atmosphere, maintained for 6 h and slowly cooled, and the product was ground to obtain Au / MgAl2O4; Loading metal Ni: The above product (Au / MgAl2O4) and 0.0024g nickel acetate tetrahydrate (99.9%) were added to a beaker, and 100mL of deionized water was added and stirred for 3h. The solution was transferred to a 500mL round-bottom flask, and evaporated in a water bath at 70℃ under negative pressure. After spin drying, the flask was placed in an oven at 90℃ and dried for 16h. The flask was scraped and the powder was ground. The powder was poured into a SiC crucible, placed in a tubular furnace, and heated from room temperature to 700℃ at a rate of 2℃ / min in a 10vol.% H2 / Ar atmosphere, maintained for 6h and slowly cooled, and ground to obtain a supported catalyst, namely Ni 0.005 -Au1 / MgAl2O4.

[0052] Comparative Example 1 The supported catalyst Ni / MgAl2O4 (based on the total molar amount of Ni and MgAl2O4, the molar content of Ni is 20%) was prepared by impregnation method, and Ni=9.3494wt% and MgAl2O4=90.6506wt% in the catalyst. The preparation steps are as follows: 0.5952 g of nickel acetate tetrahydrate (99.9%) and 1.3598 g of MgAl2O4 carrier were placed in a beaker, and deionized water was added and stirred for 3 h to fully dissolve; the solution was transferred to a 500 mL round-bottom flask, and evaporated in a water bath at 70°C under negative pressure. After spin drying, the flask was placed in an oven at 90°C and dried for 16 h, and the flask was scraped and ground to powder; the powder was poured into a SiC crucible, placed in a tubular furnace, and heated from room temperature to 700°C at a rate of 2°C / min in a 10 vol.% H2 / Ar atmosphere, maintained for 6 h and slowly cooled, and the product was ground to obtain Ni / MgAl2O4.

[0053] Comparative Example 2 The supported catalyst Co / MgAl2O4 (based on the total molar amount of Co and MgAl2O4, the molar content of Co is 20%) was prepared by impregnation method, and Co=9.3845wt% and MgAl2O4=90.6155wt% in the catalyst. The preparation steps are as follows: 0.5979 g of cobalt acetate tetrahydrate (99.5%) and 1.3592 g of MgAl2O4 carrier were placed in a beaker, and deionized water was added and stirred for 3 h to fully dissolve; the solution was transferred to a 500 mL round-bottom flask, and evaporated under negative pressure in a water bath at 70 °C. After spin drying, the flask was placed in an oven at 90 °C and dried for 16 h. The flask was scraped and the powder was ground; the powder was poured into a SiC crucible, placed in a tubular furnace, and heated from room temperature to 700 °C at a rate of 2 °C / min in a 10 vol.% H2 / Ar atmosphere, maintained for 6 h and slowly cooled, and the product was ground to obtain Co / MgAl2O4.

[0054] Comparative Example 3 Passivated catalyst Ni1-Au 0.03 / MgAl2O4 (based on the total molar amount of Ni and MgAl2O4, the molar content of Ni is 20%), prepared by multiple impregnation method. In the catalyst, Ni=9.2622wt%, Au=0.9325wt%, MgAl2O4=89.8052wt%. The preparation steps are as follows: 0.5897g of nickel acetate tetrahydrate (99.9%) and 1.3471g of MgAl2O4 carrier were placed in a beaker, and deionized water was added and stirred for 3h to fully dissolve; the solution was transferred to a 500mL round-bottom flask, and evaporated in a water bath at 70℃ under negative pressure. After spin drying, the flask was placed in an oven at 90℃ and dried for 16h, the flask was scraped and the powder was ground; the powder was poured into a SiC crucible, placed in a tubular furnace, and heated from room temperature to 700℃ at a rate of 2℃ / min in a 10vol.% H2 / Ar atmosphere, maintained for 6h and slowly cooled, and the product was ground to obtain Ni / MgAl2O4.

[0055] 0.0280 g of tetrachloroauric acid (99.9%, Au: 50%) and the Ni / MgAl2O4 prepared above were placed in a beaker, and 100 mL of deionized water was added and stirred for 3 h to fully dissolve; the solution was transferred to a 500 mL round-bottom flask, and evaporated in a water bath at 70 ° C under negative pressure. After being dried, the flask was placed in an oven at 90 ° C for 16 h, and the flask was scraped and ground to powder; the powder was poured into a SiC crucible, placed in a tubular furnace, and heated from room temperature to 700 ° C at a rate of 2 ° C / min in a 10 vol.% H2 / Ar atmosphere, maintained for 6 h and slowly cooled, and the ground product was obtained Ni1-Au 0.03 / MgAl2O4.

[0056] Comparative Example 4 Passivated catalyst Co1-Au 0.03 / MgAl2O4 catalyst (based on the total molar amount of Co and MgAl2O4, the molar content of Co is 20%), which is prepared by multiple impregnation method. In the catalyst, Co=9.2970wt%, Au=0.9322wt%, MgAl2O4=89.7708wt%. The preparation steps are as follows: 0.5924 g of cobalt acetate tetrahydrate (99.5%) and 1.3466 g of MgAl2O4 carrier were placed in a beaker, and deionized water was added and stirred for 3 h to fully dissolve; the solution was transferred to a 500 mL round-bottom flask, and evaporated in a water bath at 70°C under negative pressure. After spin drying, the flask was placed in an oven at 90°C and dried for 16 h, the flask was scraped and the powder was ground; the powder was poured into a SiC crucible, placed in a tubular furnace, and heated from room temperature to 700°C at a rate of 2°C / min in a 10 vol.% H2 / Ar atmosphere, maintained for 6 h and slowly cooled, and the product was ground to obtain Co / MgAl2O4.

[0057] 0.0280 g of tetrachloroauric acid (99.9%, Au: 50%) and the above-prepared Co / MgAl2O4 were placed in a beaker, and 100 mL of deionized water was added and stirred for 3 h to fully dissolve; the solution was transferred to a 500 mL round-bottom flask, and evaporated in a 70°C water bath under negative pressure. After being dried, the flask was placed in an oven at 90°C for 16 h, and the flask was scraped and ground to powder; the powder was poured into a SiC crucible, placed in a tubular furnace, and heated from room temperature to 700°C at a rate of 2°C / min in a 10 vol.% H2 / Ar atmosphere, maintained for 6 h and slowly cooled, and the ground product was obtained to obtain Co1-Au 0.03 / MgAl2O4.

[0058] The catalysts prepared in the examples and comparative examples were characterized by the following method: X-ray diffraction (XRD) was used to determine the crystal characteristics of the catalyst. XRD (Rigaku D / Max-RC) analysis was performed on the catalyst before and after the reaction. Cu excited Kα rays, 40kW, 100mA, λ =1.54178Å, test speed 1 ° / min, angle range 2 θ =10~80°; Field emission scanning electron microscopy (FE-SEM) was used to observe the microscopic surface morphology of the catalyst, and energy dispersive X-ray spectrum scanning (EDS-mapping) was used to analyze the distribution of metal elements on the catalyst surface. The instrument model used was GeminiSEM500. The catalyst needs to be pre-treated before the measurement. The catalyst is completely dispersed with ethanol, dripped onto the silicon wafer, placed in an oven until the ethanol is completely dry, and the silicon wafer is transferred to the sample stage, fixed with conductive glue, and the metal element distribution and microscopic morphology are observed with instruments.

[0059] Figure 1 Fresh catalyst Co 0.005 -Au1 / MgAl2O4、Ni 0.005 -XRD characterization diagram of Au1 / MgAl2O4 and fresh catalysts Co / MgAl2O4 and Ni / MgAl2O4 of comparative example. Figure 1 It can be seen that the supported catalyst Co 0.005 -Au1 / MgAl2O4、Ni 0.005 -Au1 / MgAl2O4 has an obvious Au diffraction peak, while the Co and Ni diffraction peaks are basically invisible. This is because a very small amount of Co and Ni are loaded as a single layer on the catalyst surface.

[0060] Figure 2 Fresh catalyst Co 0.005 -Au1 / MgAl2O4、Ni 0.005-SEM / Mapping (Energy spectrum scanning) image of Au1 / MgAl2O4 ( Figure 2 In the second column of the picture, in b and f, red represents Co, green represents Mg, blue represents Al, and pink represents Au; in j and n, red represents Ni, green represents Mg, blue represents Al, and pink represents Au). Figure 2 a~h correspond to fresh catalyst Co in Example 1 0.005 -Au1 / MgAl2O4, i~p corresponds to fresh catalyst Ni in Example 2 0.005 -Au1 / MgAl2O4. Figure 2 It can be seen that the active metals Ni, Co and Au are not soluble in each other but are in close contact and are dispersed on the catalyst surface in a highly dispersed form. The particle size of the catalyst is 10~300nm. Figure 1 The particle size of the fresh example catalyst is calculated from the XRD spectrum, where the particle size of Ni or Co is 1~50nm.

[0061] The catalysts prepared in the examples and comparative examples were used in high-pressure methane-carbon dioxide dry reforming reaction, and each catalyst was evaluated under high pressure. The reaction conditions were: volume ratio CH4:CO2=1:1 (H2 was introduced simultaneously, and the volume of H2 was 1% of the total volume of CH4, CO2 and H2), 850°C, 1-20bar, GHSV=6060scc·gcat -1 ·h -1 , high pressure evaluation includes CH4 conversion rate, CO2 conversion rate and product H2 / CO ratio. The outlet gas composition is analyzed by normalization method, CH4 conversion rate is calculated as shown in formula (1), CO2 conversion rate is calculated as shown in formula (2), and H2 / CO ratio is calculated as shown in formula (3) (in formula (1) to (3) "in" represents feed, "out" represents discharge): Formula (1), Formula (2): Formula (3).

[0062] Figure 3 Under the above reaction conditions, Example Co 0.005 -Au1 / MgAl2O4(a),Ni 0.005 -Au1 / MgAl2O4(b) and comparative examples Co / MgAl2O4(c), Ni / MgAl2O4(d), Co1-Au 0.03 / MgAl2O4(e) and Ni1-Au 0.03 / MgAl2O4(f) high pressure evaluation diagram, i.e. the change of CH4 conversion rate, CO2 conversion rate and product H2 / CO ratio with reaction time. Figure 3 It can be seen that under the conditions of high pressure methane-carbon dioxide reforming at 20 bar and 850 °C, the Co 0.005 -Au1 / MgAl2O4 methane initial conversion rate was 25.39%, which dropped to 23.06% after 100 h; Ni in Example 2 0.005 -The initial methane conversion rate of Au1 / MgAl2O4 was 19.85%, which dropped to 19.39% after 100h, and no obvious deactivation occurred, which showed excellent stability. Under high-pressure reaction conditions, the initial methane conversion rate of Co / MgAl2O4 in Comparative Example 2 was 62.08%, which dropped to 35.77% after 100h; the initial methane conversion rate of Ni / MgAl2O4 in Comparative Example 1 was 52.10%, which dropped to 20.32% after 100h, with obvious deactivation and a rapid decline in conversion rate. The addition of a small amount of Au as a surface passivation metal in the catalysts of Comparative Examples 3 and 4 enables Co / MgAl2O4 and Ni / MgAl2O4 to have stable and high reaction conversion rates at normal pressure, but the deactivation is obvious under pressurized conditions, and the catalyst particles are sintered after the reaction. Due to the influence of the RWGS (reverse water gas reaction) reaction, the CO2 conversion rate is higher than the CH4 conversion rate, and the H2 / CO trend is consistent with CH4 and CO2, and is less than 1.

[0063] Figure 4 Example catalyst Co 0.005 -Au1 / MgAl2O4、Ni 0.005 -XRD characterization diagram of Au1 / MgAl2O4 after reaction with comparative catalysts Co / MgAl2O4 and Ni / MgAl2O4. Figure 4 The reaction example Ni 0.005 -Au1 / MgAl2O4 and Co 0.005 -Au1 / MgAl2O4 still maintains the spinel structure. The methane conversion rate of the comparative catalysts Co / MgAl2O4 and Ni / MgAl2O4 decreased significantly under the high pressure of 20 bar, and the bed pressure drop increased significantly. The XRD characterization showed obvious carbon deposition diffraction peaks, and the active metal particle size increased significantly after the reaction, and there was sintering phenomenon.

[0064] Figure 5 Example catalyst Co 0.005 -Au1 / MgAl2O4、Ni 0.005 -Thermogravimetric curves of Au1 / MgAl2O4 after reaction with comparative catalysts Co / MgAl2O4 and Ni / MgAl2O4, Figure 5(a) is CO2-TGA, (b) is Air-TGA. Figure 5 Example Ni after display reaction 0.005 -Au1 / MgAl2O4 and Co 0.005 -Au1 / MgAl2O4 has almost no carbon deposit production and has very good anti-sintering and anti-carbon deposition properties.

[0065] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A supported catalyst, characterized in that The invention comprises a MgAl2O4 carrier and a metal component supported on the surface of the MgAl2O4 carrier, wherein the metal component comprises Au particles and a transition metal dispersed on the surface of the Au particles, wherein the transition metal is Ni or Co, and the molar ratio of the transition metal to the Au particles is (0.5-5):100, and the mass content of the transition metal in the supported catalyst is greater than 0.006% and less than 0.06%.

2. The supported catalyst according to claim 1, characterized in that The particle size of the supported catalyst is 10-300 nm, and the particle size of the transition metal in the supported catalyst is 1-50 nm.

3. The method for preparing a supported catalyst according to claim 1 or 2, characterized in that: The following steps are involved: Mixing urea, a soluble aluminum salt, a soluble magnesium salt and water for hydrothermal reaction to obtain a precipitate; The precipitate is sequentially dried and first calcined to obtain a MgAl2O4 carrier; The MgAl2O4 carrier is mixed with a soluble gold source and water for a first impregnation, and then concentrated, dried and second calcined in sequence to obtain a MgAl2O4 carrier loaded with Au; The Au-loaded MgAl2O4 carrier is mixed with the soluble salt of the transition metal and water for a second impregnation, and then concentrated, dried and calcined for a third time in sequence to obtain the supported catalyst; the second calcination and the third calcination are both carried out in a reducing atmosphere.

4. The preparation method according to claim 3, characterized in that: The molar ratio of the urea, the aluminum element in the soluble aluminum salt and the magnesium element in the soluble magnesium salt is (2-4):2:1; the temperature of the hydrothermal reaction is 120-140° C., and the time is 12-16 hours.

5. The preparation method according to claim 3, characterized in that: The first calcination includes a first stage and a second stage which are performed sequentially. The temperature of the first stage is 400-550° C. and the insulation time is 1-2 hours. The temperature of the second stage is 600-900° C. and the insulation time is 6-8 hours.

6. The preparation method according to claim 3, characterized in that: The first impregnation time is 2-5 hours; the second roasting temperature is 600-900° C., and the heat preservation time is 6-8 hours.

7. The preparation method according to claim 3, characterized in that: The second impregnation time is 2-5 hours; the third calcination temperature is 600-900° C., and the heat preservation time is 6-8 hours.

8. The preparation method according to claim 3, 6 or 7, characterized in that: The reducing atmosphere is a mixture of hydrogen and argon, and the volume percentage of hydrogen in the mixture is 10%.

9. Use of the supported catalyst according to claim 1 or 2 or the supported catalyst prepared by the preparation method according to any one of claims 3 to 8 in the dry reforming reaction of methane and carbon dioxide under catalytic high-pressure conditions, wherein the pressure of the dry reforming reaction of methane and carbon dioxide is 1 to 20 bar and the temperature is 800 to 900°C.

10. The use according to claim 9, characterized in that: In the dry reforming reaction of methane and carbon dioxide, the volume ratio of CH4 to CO2 is 1:1, and the space velocity GHSV is 3030~30300scc·gcat -1 ·h -1 .

Citation Information

Patent Citations

  • Dry-gas reforming catalyst for methane and preparation method for dry-gas reforming catalyst for methane

    CN106512999A

  • Magnesia alumina spinel and high temperature methanation catalyst and preparation methods thereof

    CN106518045A

  • Synthesis of trimetallic nanoparticles by homogeneous deposition precipitation, and application of the supported catalyst for carbon dioxide reforming of methane

    CN107108206A

  • Reforming catalyst, preparation method and application thereof, and method for preparing synthesis gas by dry reforming of methane and carbon dioxide

    CN117943031A

Cited By

  • MgAl2O4 carrier as well as preparation method and application thereof

    CN121103341A

  • MgAl2O4 carrier, and preparation method and application thereof

    CN121103341B